Becoming French : mapping the geographies of French identity, 1871-1914 - Lindaman, Dana Kristofor (Northwestern University Press, 2016)
Becoming French explores the geographical shift that occurs in French society during the first four decades of France's Third Republic government. Dana Kristofor Lindaman provides the historical context that led to the explosion of geographic interest at the end of the nineteenth century, exploring the ways that the work of the geographers Paul Vidal de la Blache and Élisee Reclus served as a conceptual basis for abstract notions of the nation such as la Patrie. Lindaman then uses Reclus's formulation of the earth as "une organisme terrestre" (terrestrial organism) to read Jules Verne's Voyage au centre de la terre (Journey to the Center of the Earth) as a journey to the center of the individual self. Finally, he traces the geographic narrative of G. Bruno's Tour de la France par deux enfants, in particular the way that Bruno's work incorporates the geographic thought of Vidal de la Blache, to discover the organic ties that bind readers through the shared experience of reading the text.